Propiedades Físicas Y Mecánicas De Tres Especies Forestales: Piptocoma Discolor (Kunth.) Pruski (Pigüe), Iriartea Deltoidea Ruiz & Pav. (Chonta) Y Pouteria Glomerata (Intachi) - Morejón, Elizabeth; Lara, Ximena; Cabezas, Erika; Román, Danilo; Salazar, Eduardo (European Scientific Journal, ESJ, 2018)
This research was developed to determine the physical and mechanical properties of three forestry species such as: Piptocoma discolor (Kunth) Prusky (Pigüe), Iriartea deltoidea Ruiz & Pav. (Chonta) and Pouteria glomerata (Intachi); thus giving the suitable use to each specie according to their response to the tests. The tests were done at ESPOCH laboratories, using the lab from the irrigation experimental center of the Natural resources faculty for checking the physical properties of humidity and density. The lab from Material resistance of the mechanical Faculty was used to check the mechanical properties. This study is quite important due to the lack of information researched on all the specie properties. One example would be the Pigüe case, which has been used for fruit boxing, the same that presents better qualities than Intachi and it can be perfectly used in building poles and pillars even at decks because of its light, soft and easy-to-cut wood. The Intachi is an excellent kind of Wood used for floors and the Chonta used for bridges and outsides because of its hard and strong wood.